2009
DOI: 10.1039/b915400k
|View full text |Cite
|
Sign up to set email alerts
|

On the ionization and dissociative photoionization of iodomethane: a definitive experimental enthalpy of formation of CH3I

Abstract: The dissociative photoionization onset energy of the CH(3)I --> CH(3)(+) + I reaction was studied at the vacuum ultraviolet (VUV) beamline of the Swiss Light Source (SLS) using a new imaging photoelectron photoion coincidence (iPEPICO) apparatus operating with a photon resolution of 2 meV and a threshold electron kinetic energy resolution of about 1 meV. Three previous attempts at establishing this value accurately, namely a pulsed field ionization (PFI)-PEPICO measurement, ab initio calculations and a mass-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 45 publications
10
101
1
Order By: Relevance
“…Based on a previous study of Ar, N 2 , and CH 3 I, 22 the threshold photoelectron peak positions could be expected to be Stark shifted 23 by 5 meV to lower energy when applying the higher field. In the same study, 22 field effects were found not to play a role in off-resonance threshold photoionization, which suggests that autoionization can compete effectively with field ionization in the absence of long-lived Rydberg states. In C 2 F 4 + , the TPES peak positions did not shift measurably as a function of the field strength, indicating fast autoionization and neutral decay channels for high-n Rydberg states.…”
Section: A Experimentalmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on a previous study of Ar, N 2 , and CH 3 I, 22 the threshold photoelectron peak positions could be expected to be Stark shifted 23 by 5 meV to lower energy when applying the higher field. In the same study, 22 field effects were found not to play a role in off-resonance threshold photoionization, which suggests that autoionization can compete effectively with field ionization in the absence of long-lived Rydberg states. In C 2 F 4 + , the TPES peak positions did not shift measurably as a function of the field strength, indicating fast autoionization and neutral decay channels for high-n Rydberg states.…”
Section: A Experimentalmentioning
confidence: 98%
“…Furthermore, directC-state involvement is not necessarily required in threshold photoionization. In the CH 3 I study, 22 it was proposed that the neutral parent can be excited to the Rydberg manifold in the initial step. The Rydberg manifolds belonging to each ion state will have the similar characteristics to the ion state, and autoionization may also occur after internal conversion.…”
Section: F-atom Loss From C 2 H 3 Fmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also essential when cooling the sample in a supersonic molecular beam, which generates a variety of clusters along with the cooled sample of interest. A recent example shown by Bodi at the conference (which may be the first of its kind) is shown in Figure 1 for the case of methyl iodide cooled in a seeded Ar beam [19]. The dominant species in the total TPES (solid points) is ascribed to the cold CH 3 I.…”
Section: A Synchrotron-based Vuv Threshold Photoelectron Spectroscopmentioning
confidence: 93%
“…Recent threshold photoelectron photoion coincidence (TPEPICO) experiments, in which both the photon and the photoelectron energies are known to within 1-2 meV (0.1-0.2 kJ mol -1 ), [1,[10][11][12] are capable of measuring dissociative photoionization onset energies in small to medium sized molecules with such levels of accuracy. To reiterate, in the absence of an overall reverse barrier, the onset energies, E 0 , correspond to the reaction energy at 0 K, and yield the enthalpies of formation for the parent ion, daughter ion or neutral fragment if two out of the three are known;…”
Section: Introductionmentioning
confidence: 99%